Factors Associated with Iranian Couple\'s Communication Patterns: A Scoping Review - Sedigheh Hasani-Moghadam; Jila Ganji; Hamid Sharif Nia; Mohsen Aarabi; Soghra Khani (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Couples' communication patterns is of great importance in resolving marital conflicts. These patterns include mutual constructive communication, mutual avoidance communication, and demand-withdrawal communication. The present study aimed at investigating the factors associated with Iranian couples' communication patterns. Materials and methods: A scoping review was performed at five stages; 1-designing the research question 2- searching and extracting research studies 3- selecting relevant studies 4- organizing and summarizing the information, 5. reporting the results. Results: In this scoping review, 18 articles were selected from 130 studies. The factors affecting couples' communication patterns were classified into four categories: 1- spiritual well-being and spirituality, 2- marital and sexual satisfaction, 3- marital compatibility, and 4- love styles. Conclusion: Some factors, including spiritual well-being and spirituality, marital satisfaction and sexual satisfaction, marital compatibility, and love styles were found to affect couples' communication patterns. Seemingly providing ways to enhance couples' communication patterns towards a mutual constructive pattern is necessary to prevent marital problems and conflicts, and experiencing effective and efficient relationships.